1991
DOI: 10.1212/wnl.41.5.644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphatidylserine in age‐associated memory impairment

Abstract: We treated 149 patients meeting criteria for age-associated memory impairment (AAMI) for 12 weeks with a formulation of phosphatidylserine (100 mg BC-PS tid) or placebo. Patients treated with the drug improved relative to those treated with placebo on performance tests related to learning and memory tasks of daily life. Analysis of clinical subgroups suggested that persons within the sample who performed at a relatively low level prior to treatment were most likely to respond to BC-PS. Within this subgroup, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(98 citation statements)
references
References 0 publications
2
95
0
1
Order By: Relevance
“…Milk fat globule membrane (MFGM) phospholipids have been shown to have a number of health benefits [4,5,8,9,15], and MFGM material may be successfully used to stabilize emulsions [3,20,21,32] and produce liposomes [29].…”
Section: Introductionmentioning
confidence: 99%
“…Milk fat globule membrane (MFGM) phospholipids have been shown to have a number of health benefits [4,5,8,9,15], and MFGM material may be successfully used to stabilize emulsions [3,20,21,32] and produce liposomes [29].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical investigations have also shown that B-PS treatment can improve Alzheimer's disease (AD) and related cognitive disorders (8,9). Sakai et al (10) prepared soybean leci thin transphosphatidylated phosphatidylserine (SB-tPS) from soybean phosphatidylcholine by transphosphati dylation using phospholipase D, and they found that the intravenous or intraperitoneal administration of SB-tPS increases brain glucose concentrations in mice and antagonizes amnesic effects of scopolamine (SCP) in rats, as did B-PS.…”
mentioning
confidence: 99%
“…Research on the substances has produced mixed findings. In one study, 149 patients who met the criteria for age-associated memory impairment were treated for 12 weeks with a formulation of phosphatidylserine or placebo (Crook et al, 1991). Patients in the treatment group improved on performance tests related to learning and memory and tasks of daily life.…”
Section: Phosphadtidylserine and Phosphatidylcholinementioning
confidence: 99%